2009
DOI: 10.3892/ijo_00000394
|View full text |Cite
|
Sign up to set email alerts
|

LIV-1 enhances the aggressive phenotype through the induction of epithelial to mesenchymal transition in human pancreatic carcinoma cells

Abstract: Abstract. LIV-1 is a downstream target of STAT3 and is essential for the nuclear localization of Snail, a master regulator of epithelial to mesenchymal transition (EMT). Little is known about the association of LIV-1 with pancreatic carcinoma development, therefore, expression of LIV-1 mRNA was analyzed by real-time reverse transcriptase polymerase chain reaction (RT-PCR) in 9 cultured cell lines (8 carcinoma and 1 normal duct cell lines) and 24 pancreatic tissues (12 carcinoma and 12 normal tissues). Localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For instance, once activated, STAT3, in combination with estrogen receptor (ER), binds to the LIV-1 promoter leading to the induction of LIV-1 expression, followed by proteolytic N-terminal cleavage of the LIV-1 protein and its subsequent translocation to the plasma membrane. Subsequently, LIV-1 stabilizes Snail through inactivation of GSK3β [24][25][26]. In addition, RANKL is known to enhance EMT in prostate cancer through the STAT3/LIV-1 axis [27].…”
Section: Role Of Il-6/jak/stat3 In the Induction Of Emtmentioning
confidence: 99%
“…For instance, once activated, STAT3, in combination with estrogen receptor (ER), binds to the LIV-1 promoter leading to the induction of LIV-1 expression, followed by proteolytic N-terminal cleavage of the LIV-1 protein and its subsequent translocation to the plasma membrane. Subsequently, LIV-1 stabilizes Snail through inactivation of GSK3β [24][25][26]. In addition, RANKL is known to enhance EMT in prostate cancer through the STAT3/LIV-1 axis [27].…”
Section: Role Of Il-6/jak/stat3 In the Induction Of Emtmentioning
confidence: 99%
“…Data for ER, PgR, HER2, Ki67, GATA3, FOXA1 and TFF1 were available as previously published [ 13 , 15 , 18 , 21 ] [ 31 ]. ER and PgR positivity were defined as positive nuclear staining in ≥ 1% of the invasive tumour cells [ 13 , 21 , 23 ]; 75% of the patients had ER + tumours. HER2 positivity was defined as strong positive membranous staining in ≥ 10% of the invasive tumour cells (score + 3).…”
Section: Slc39a6 Protein Expression ( Nottingham Cohort)mentioning
confidence: 99%
“…Overexpression of SLC39A6 has been related to the progression of several types of cancer, including breast [ 13 , 18 ], prostate [ 21 ], pancreatic [ 23 ], cervical [ 24 ] and liver cancer [ 25 ]. An in vitro study suggested that SLC39A6 is involved in metastasis in BC, as overexpression of SLC39A6 promoted the epithelial-mesenchymal transition (EMT) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%